Produtos notáveis no 8º ano do Ensino Fundamental II: contribuições da utilização de diferentes recursos didáticos - Dario, Érica Maria Rennó Villela (2017)
This study aims to investigate how students of 8th grade elementary school explore different registers of semiotic representation involving notable products, with the use of didactic resources such as satin vinyl foam - E.V.A. and GeoGebra software. We intend to characterize teaching and learning so that students understand and / or solve problems related to remarkable products. Studies that have analyzed the learning level of algebraic concepts have suggested that the use of concrete material aimed at learning these concepts has facilitated the understanding of mathematical contents. Question of research: "How do students of the 8th grade elementary school explore different registers of semiotic representation involving remarkable products?" In our analyzes we are based on Duval's Theory of Semiotic Representation Records and On Theory of They thrive, through activities that seek to favor the learning of remarkable products. The research is considered qualitative and involves an intervention study with six students from a private school in São Paulo. The students participated in three meetings, each lasting two hours, developing the activities in pairs. The results indicate contributions with the use of didactic resources - E.V.A. and GeoGebra software, which had a mediating role favoring the learning of notable products for evidencing and treating conceptual errors. In addition, conversions and treatments of semiotic representation records could show possibilities of handling and manipulation of objects constructed with E.V.A material. and the representation of the objects and their movement in a system of axes in GeoGebra software